(untitled) (Bangladesh Journal of Child Health, 2024)
Background: Use of drugs without any prior medical consultation is a common practice in lower and middle income countries which causes health hazards and misuse or overuse of drugs. Fever is a common symptom for which parents seek medical care according to their knowledge and ability. Objective: To observe the patterns of drug use, source of drugs, and identify the factors associated with the use of non-prescription drugs in febrile children. Methods: This is a hospital based observational cross sectional study conducted over a period of four months in the Ashulia Women and Children Hospital (AWCH). Study population was the febrile children attending paediatric out patient department. Data was collected from parents/caregiver through a pretested questionnaire. Result: Among 614 study children 77.2% had fever for less than 5 days and out of them 544(90.7%) children were treated with different types of drugs. Out of them 90.1% children had drugs without any prescription mostly from drug retailers (54.8%). Commonly used drug was antipyretic (99.3%) followed by antibiotic (49.1%) and antihistamine (31.9%) and 73.16% children were treated with multiple drugs. Cefixime (40.8%) was found to be a widely used antibiotic. Perception of mild illness (53.3%) was reported predominantly as a cause of using drugs without medical advice. Conclusion: This study reveals use of multiple drugs including antibiotics for treating febrile illness of children prior to medical consultation and treatment was most commonly taken from drug retailers. BANGLADESH J CHILD HEALTH 2023; VOL 47 (1) : 39-42